Corticosteroids in Pneumococcal Meningitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The records of 97 infants and children with pneumococcal meningitis, 41 receiving corticosteroid therapy, were examined at the Department of Pediatrics, University of Texas Southwestern Medical Center, Dallas, Texas.